2013
DOI: 10.1097/brs.0b013e31829c2e12
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation of Spine

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The earliest RFAs were performed with monopolar electrodes which could only create the maximal coagulation diameter of 1.6 cm and were not adequate for most tumors. However, as modification of RFA electrode design has advanced with development of multiprobe arrays, bipolar arrays, internally cooled electrodes and cluster or pulsed radiofrequency, a significantly increased coagulation area can now be achieved [25] . After studying radiofrequency ablation in pig spine with an internally cooled electrode containing an adjustable tip, You et al [25] found that the coagulation area was 4.19 ± 2.95 cm 3 (1.26–3.05 cm in diameter) in an in vitro experiment but 6.80 ± 2.72 cm 3 (1.28–2.51 cm in diameter) in an in vivo experiment, with the average temperature in the epidural space of the pig of 34.9 °C at the end of 20-min ablation but 38.2 °C at the end of 30-min ablation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest RFAs were performed with monopolar electrodes which could only create the maximal coagulation diameter of 1.6 cm and were not adequate for most tumors. However, as modification of RFA electrode design has advanced with development of multiprobe arrays, bipolar arrays, internally cooled electrodes and cluster or pulsed radiofrequency, a significantly increased coagulation area can now be achieved [25] . After studying radiofrequency ablation in pig spine with an internally cooled electrode containing an adjustable tip, You et al [25] found that the coagulation area was 4.19 ± 2.95 cm 3 (1.26–3.05 cm in diameter) in an in vitro experiment but 6.80 ± 2.72 cm 3 (1.28–2.51 cm in diameter) in an in vivo experiment, with the average temperature in the epidural space of the pig of 34.9 °C at the end of 20-min ablation but 38.2 °C at the end of 30-min ablation.…”
Section: Discussionmentioning
confidence: 99%
“…However, as modification of RFA electrode design has advanced with development of multiprobe arrays, bipolar arrays, internally cooled electrodes and cluster or pulsed radiofrequency, a significantly increased coagulation area can now be achieved [25] . After studying radiofrequency ablation in pig spine with an internally cooled electrode containing an adjustable tip, You et al [25] found that the coagulation area was 4.19 ± 2.95 cm 3 (1.26–3.05 cm in diameter) in an in vitro experiment but 6.80 ± 2.72 cm 3 (1.28–2.51 cm in diameter) in an in vivo experiment, with the average temperature in the epidural space of the pig of 34.9 °C at the end of 20-min ablation but 38.2 °C at the end of 30-min ablation. After evaluation of a bipolar-cooled RFA device for bone metastases in porcine vertebrae, Pezeshki et al [26] found that the coagulation necrosis volume created by this bipolar device was 2.24 ± 0.90 cm 3 with the mean temperature on the surface of the vertebral body of 36.1 °C (range 32–40 °C) at the end of 15-min ablation.…”
Section: Discussionmentioning
confidence: 99%